2003
DOI: 10.1124/mol.64.5.1076
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Invasion and Angiogenesis by Zinc-Chelating Agent Disulfiram

Abstract: Cell invasion and angiogenesis are crucial processes in cancer metastasis that require extracellular matrix (ECM) degradation. Proteolytic degradation of the ECM components is a central event of invasion and angiogenesis processes. During these processes, matrix metalloproteinases (MMPs) seem to be primarily responsible for much of the ECM degradation. Disulfiram is frequently used in the treatment of alcoholism and has been reported to possess antiretroviral activity and can eject intrinsic zinc out of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 41 publications
1
71
1
Order By: Relevance
“…Disulfiram, a drug marketed as an alcohol dehydrogenase inhibitor (Antabuse), is also known for its zinc-ejecting properties (17,18). Most recently, disulfiram was described to inhibit angiogenesis and invasion of human tumor and umbilical vein endothelial cells owing to their dependence on zinc chelating proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disulfiram, a drug marketed as an alcohol dehydrogenase inhibitor (Antabuse), is also known for its zinc-ejecting properties (17,18). Most recently, disulfiram was described to inhibit angiogenesis and invasion of human tumor and umbilical vein endothelial cells owing to their dependence on zinc chelating proteins.…”
Section: Discussionmentioning
confidence: 99%
“…16,17). Disulfiram was chosen because it is known as a potent, but general, zinc ejector (17,18), whereas NSC667089 very specifically inhibits the HIV type 1 nucleocapsid p7 zinc finger (16). Drug stocks (100 mmol/L) were prepared in DMSO and diluted to 100 Amol/L in 1Â ubiquitination assay reaction buffer (see above).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that DSF could inhibit cancer cell invasion by interacting with matrix metalloprotease 2 (MMP-2) and MMP-9 and inhibiting their proteolytic activities via chelating zinc [81]. An observation from another group suggested that antitumor activity of DSF in melanoma and hepatic tumor could be potentiated by Zn 2+ supplementation [82].…”
Section: Drugs In Dithiocarbamate Familymentioning
confidence: 99%
“…Why metal ionophores should selectively kill cancer cells in vivo is unclear, but the fact that they are tolerated by animals and humans is encouraging. Disulfiram, for example, a drug that is hydrolyzed into dithiocarbamates in vivo, has a long track record of safety in humans and has demonstrated anticancer and antiangiogenic activity (55,56). The cancer-specificity of these compounds may lie in their ability to alter metabolic signatures, such as NF-kappa B overexpression, that are unique to cancer cells.…”
Section: Will Metal Ionophores Be Clinically Useful?mentioning
confidence: 99%